Domestic energy consumption in Ghana: Deprivation versus likelihood of access - Alhassan A. Karakara; Evans Osabuohien; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
Purpose - This paper analyses the extent to which households are deprived (or otherwise) of clean energy sources in Ghana. Design/methodology/approach - It engages the Ghana Demographic and Health Survey data (GDHS VI). Three different energy deprivation indicators were estimated: cooking fuel deprivation, lighting deprivation and indoor air pollution. The empirical evidence is based on logit regressions that explain whether households are deprived or not. Findings - The results show that energy deprivation or access is contingent on the area of residence. Energy access and deprivation in Ghana show some regional disparities, even though across every region, the majority of households use three fuel types: Liquefied Petroleum Gas (LPG), charcoal and wood cut. Increases in wealth and education lead to reduction in the likelihood of being energy deprived. Thus, efforts should be geared towards policies that will ensure households having access to clean fuels to reduce the attendant deprivations and corresponding effects of using dangerous or dirty fuels. Originality/value - This study complements the extant literature by analysing the extent to which households are deprived (or otherwise) of clean energy sources in Ghana.
Keywords: O13; P28; Q42; 330; Energy deprivation; Ghana; Households; Sustainable development